Assessing the performance of a physically based hydrological model using a proxy‐catchment approach in an agricultural environment. Issue 24 (13th September 2019) - Escobar‐Ruiz, Veronica; Smith, Hugh G.; Blake, William H.; Macdonald, Neil
Abstract: Physically based models are useful frameworks for testing intervention strategies designed to reduce elevated sediment loads in agricultural catchments. Evaluating the success of these strategies depends on model accuracy, generally established by a calibration and evaluation process. In this contribution, the physically based SHETRAN model was assessed in two similar U.K. agricultural catchments. The model was calibrated on the Blackwater catchment (18 km 2 ) and evaluated in the adjacent Kit Brook catchment (22 km 2 ) using 4 years of 15 min discharge and suspended sediment flux data. Model sensitivity to changes in single and multiple combinations of parameters and sensitivity to changes in digital elevation model resolution were assessed. Model flow performance was reasonably accurate with a Nash–Sutcliffe efficiency coefficient of 0.78 in Blackwater and 0.60 in Kit Brook. In terms of event prediction, the mean of the absolute percentage of difference ( μAbs diff ) between measured and simulated flow volume ( Qv ), peak discharge ( Qp ), sediment yield ( Sy ), and peak sediment flux ( Sp ) showed larger values in Kit Brook (48% [ Qv ], 66% [ Qp ], 298% [ Sy ], and 438% [ Sp ]) compared with the Blackwater catchment (30% [ Qv ], 41% [ Qp ], 106% [ Sy ], and 86% [ Sp ]). Results indicate that SHETRAN can produce reasonable flow prediction but performs less well in estimation of sediment flux, despite reasonably similar hydrosedimentary behaviour between catchments. The sensitivity index showed flow volume sensitive to saturated hydraulic conductivity and peak discharge to the Strickler coefficient; sediment yield was sensitive to the overland flow erodibility coefficient and peak sediment flux to raindrop/leaf soil erodibility coefficient. The multiparameter sensitivity analysis showed that different combinations of parameters produced similar model responses. Model sensitivity to grid resolution presented similar flow volumes for different digital elevation model resolutions, whereas event peak and duration (for both flow and sediment flux) were highly sensitive to changes in grid size. Abstract : Model flow performance showed Nash‐Sutcliffe efficiency coefficient (NSE) of 0.78 in Blackwater and 0.60 in Kit Brook. Event prediction using the mean of the absolute percentage of difference (μAbsdiff ) between measured and simulated data ( Qv, Qp, Sy and Sp ) showed larger values in Kit Brook than Blackwater; corresponding to similar R 2 in Qv and Qp, but higher for Sy and Sp . The proxy‐catchment test demonstrated that SHETRAN can predict event‐scale flow with reasonable accuracy, requiring catchment‐specific calibration for sediment prediction.